Success Factors of Village-Owned Enterprises (BUMDes) Performance in Indonesia: An Exploratory Study - Hafiez Sofyani; Randi Atmaja; Sri Budhi Rezki (Universitas Muhammadiyah Yogyakarta, Indonesia, 2019)
The full autonomy given to village governments by the Indonesian government coming with the demand to establish Village-Owned Enterprises (BUMDes) brings both opportunities and challenges. The reason is that not all BUMDes which have been established could perform satisfactorily. In fact, out of 3900 existing BUMDes, only a small percentage showed satisfactory performance. Based on this background, this research aims to investigate key success factors which drive the performance of BUMDes. The research was conducted from November to December 2018. The research subjects were BUMDes Amarta, Srimartani Makmur, and Tirtonirmolo, which are located in the Special Region of Yogyakarta, Indonesia. These three BUMDes were chosen because they serve as a benchmark for how BUMDes in Indonesia should be managed. The research informants were directors and employees of these BUMDes where each BUMDes was represented by one director and one employee. The data were obtained from direct interviews and documentation. The data were analyzed using a qualitative approach, consisting of such steps as data reduction, data display and conclusion drawing. The results indicated that the factors that drive the performance of BUMDes were BUMDes employees’ patriotism and passion, skills, training, level of education, experience, honesty (ethical behavior), having a sense of responsibility, sincerity, seriousness, caring for the environment and society, being resilient, cohesiveness of teamwork, transparent communication between BUMDes managers, never-give-up attitude in trying to achieve the performance targets, religiosity, work satisfaction, visionary (transformational) leadership style, and the presence of incentive mechanisms.